2008
DOI: 10.1016/j.jvs.2007.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reliability and utility of skin perfusion pressure measurement in ischemic limbs—Comparison with other noninvasive diagnostic methods

Abstract: Our results suggest that measurement of SPP is an objective method for assessing the severity of peripheral arterial disease or for predicting wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 25 publications
4
151
0
2
Order By: Relevance
“…1, C and D). The pair-matched SPP recorded in the intact pig skin tightly matched the values seen in healing wounds (67). Fullthickness biopsy wounds were placed on the ischemic tissue or adjacent nonischemic tissue as shown in Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…1, C and D). The pair-matched SPP recorded in the intact pig skin tightly matched the values seen in healing wounds (67). Fullthickness biopsy wounds were placed on the ischemic tissue or adjacent nonischemic tissue as shown in Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Among a number of noninvasive diagnostic methods, measurement of the SPP has proven utility for assessing the severity of ischemia at the wound site. Measurement of SPP represents an objective approach to assess the severity of peripheral arterial disease or for predicting wound healing (53,67). SPP measurements from the above-described bipedicle flaps and comparison with SPP measured from the adjacent intact skin demonstrated that the bipedicle flaps had an SPP consistent with the SPP of chronic nonhealing wounds (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The postoperative SPP values in group N were better than those in group U but less than those in group H. Compared with group H, group N featured more patients with chronic kidney disease and group U had even more. Additionally, groups N and U included more patients with diabetes than group H; therefore, the patients in groups N and U could have had more advanced distal lesions than did the patients in group H. [12][13][14] Previous studies have suggested a value of 30 mmHg 1,2,6) or 40 mmHg 4,5) to be the critical SPP threshold necessary for wound healing. In the present study, 50% of the limbs had a mean postoperative SPP value of <30 mmHg in group U, consistent with the results of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6] We started SPP measurements following the establishment of a vascular laboratory at our institution in August 2008. Although the number of examinations of SPP is still small in our institution at present, we deemed it useful to have an initial evaluation of its effectiveness by retrospectively assessing the changes in SPP values obtained between the pre-and postoperative periods 8,9) and the relationship between the SPP values and ulcer healing, in order to assess the utility of SPP measurement in evaluating the outcome of arterial reconstructions in patients with CLI caused by arteriosclerosis obliterans (ASO).…”
Section: Skin Perfusion Pressure Measurement To Assess Improvement Inmentioning
confidence: 99%
See 1 more Smart Citation